2018
DOI: 10.3390/nu10111572
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Considerations When Balancing the Risks of Contaminants with the Benefits of Fruits and Vegetables for Infants and Toddlers

Abstract: Background: Fruits and vegetables are key to a healthy diet, particularly in children; however, parents may be concerned about contaminants found in fruits and vegetables. Making informed food choices for children requires understanding and balancing the risks of contaminant exposure with the importance of providing a healthy diet. The objective of this work is to identify fruits and vegetables commonly consumed by infants and toddlers; identify potential contaminants in fruits and vegetables; and outline cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
0
6
0
2
Order By: Relevance
“…The analyses in this study focused on measuring As, Cd, Hg, and Pb levels in different baby food types (e.g., fruits, grains, root vegetables, and leguminous vegetables). Previous studies identified these heavy metals as chemicals of concern for children’s exposures, owing either to their concentrations in foods or to childhood-specific hazards [ 2 , 4 , 11 , 29 ]. We used results of these analyses to estimate non-cancer and cancer health risks for children <1 year, 1 to <2 years, and 2 to <3 years, along with cumulative cancer risks across all ages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The analyses in this study focused on measuring As, Cd, Hg, and Pb levels in different baby food types (e.g., fruits, grains, root vegetables, and leguminous vegetables). Previous studies identified these heavy metals as chemicals of concern for children’s exposures, owing either to their concentrations in foods or to childhood-specific hazards [ 2 , 4 , 11 , 29 ]. We used results of these analyses to estimate non-cancer and cancer health risks for children <1 year, 1 to <2 years, and 2 to <3 years, along with cumulative cancer risks across all ages.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting identified elements were As, Cd, Hg, and Pb. Previous studies have identified these elements and the importance of characterizing their risks to infants and young children [ 2 , 4 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…It was based on dietary survey's including a 24-h dietary recall and feeding practices questionnaire conducted with 3,248 caregivers and was the largest cross-sectional dietary intake survey of its time in the US focused on children ( 18 ). Using data from the most recent US Food and Drug Administration's Total Diet Studies (FDA TDS) and estimations of average intake of specific foods from FITS 2016 data, Callen et al ( 19 ) identified the presence of lead, cadmium, arsenic, and mercury in several baby foods. This study was limited by the fact that it extrapolated data from two separate surveys and did not evaluate the contaminant intake risk.…”
Section: Analysis and Quantification Of Heavy Metalsmentioning
confidence: 99%
“…Nigeria's annual fruit import value is to the tune of millions of dollars with the attendant flooding of our local markets and grocery stores with imported fruits (European Commission, 2020). Fruit importation not only kills the awareness and development of indigenous fruits but also comes with health risks associated with the chemical preservatives used to prevent the fruits from deterioration and decay during the long period of shipping and storage before sale (Callen et al 2018). These chemical preservatives have been associated with the increased incidence of diseases such as cancer and other deadly sicknesses in the country (Sharma, 2015).…”
Section: Introductionmentioning
confidence: 99%